2017
DOI: 10.3174/ajnr.a5096
|View full text |Cite
|
Sign up to set email alerts
|

Benign Miliary Osteoma Cutis of the Face: A Common Incidental CT Finding

Abstract: BACKGROUND AND PURPOSE:Osteoma cutis of the face represents a primary or secondary formation of ossific foci in the facial skin. Its primary form has been sparsely described in the plastic surgery and dermatology literature. As radiologists, we routinely encounter incidental, very small facial calcified nodules on CT studies performed for a variety of unrelated reasons. We hypothesized that this routinely encountered facial calcification represents primary miliary osteoma cutis and is a common, benign, age-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 15 publications
(21 reference statements)
0
17
0
Order By: Relevance
“…So far, 70 cases of MMOC have been reported. In a recent radiological study, Kim et al (6) described facial calcified nodules compatible with miliary osteomas as a very common finding in routine CT images of the head, suggesting that MMOC is probably underdiagnosed. In 1928 Hopkins first suggested the association with acne and afterwards a previous history of acne has been described in 55% of cases of MMOC (5).…”
Section: Discussionmentioning
confidence: 99%
“…So far, 70 cases of MMOC have been reported. In a recent radiological study, Kim et al (6) described facial calcified nodules compatible with miliary osteomas as a very common finding in routine CT images of the head, suggesting that MMOC is probably underdiagnosed. In 1928 Hopkins first suggested the association with acne and afterwards a previous history of acne has been described in 55% of cases of MMOC (5).…”
Section: Discussionmentioning
confidence: 99%
“…Authors regard MMOC as uncommon [22], rare [3,7,10,12,13], or very rare [14], while a few consider it as a relatively common, but under-recognized, condition [5,15,75]. Previous and recent imaging studies support this latter view.…”
Section: Epidemiologymentioning
confidence: 99%
“…Kishi et al [76] performed a dental radiographic study and found skin osteomas in 2.2% (48 of 2,089) subjects, while Shigehara et al [77] reported an incidence of 27.8% (44 of 158) based on a similar X-ray investigation. More recently, Kim et al [75] conducted a retrospective analysis of 1,315 sinus computerized tomography (CT) scans and identified a 42.1% prevalence of facial calcified nodules. It is interesting that these lesions were mostly found on the frontal and maxillary regions, overlapping the preferential distribution of osteomas identified in this review.…”
Section: Epidemiologymentioning
confidence: 99%
“…Past and recent imaging studies found incidental skin osteomas and calcified nodules of the face ranging from 27.8% to 42.1% in routine X-ray and computed tomography (CT) scan analysis, respectively. 5,6 MMOC is then seemingly under-diagnosed with mostly subclinical lesions passing under the radar during clinical examination leading to only obvious cases of aesthetically conscious patients consulting for such condition. Misdiagnosis and the benign behaviour of the condition may also contribute to under-reporting.…”
Section: Introductionmentioning
confidence: 99%